Nutrition, infection and child growth in Papua New Guinea - Ulijaszek, S (Collegium Antropologicum/ Croatian Anthropological Society, 2000)
Growth patterns of populations in Papua New Guinea (PNG) have traditionally shown considerable variation, with the greatest difference lying between coastal and highland populations. While genetic differences in explaining these patterns cannot be excluded, the generally poor growth relative to western growth references is largely due to the complex interactive effects of undernutrition and infection. The effects of diet, nutrition and infection on the nutritional status of a child vary with age, the general disease ecology and the type and extent of exposure to it, patterns of infant and young child feeding, and types of food consumed. There are two possible ways in which the relationship between undernutrition and infection can begin; one in which poor nutritional status leads to impaired immunocompetence and reduced resistance to infection, and the other in which exposure to infectious disease can lead to a range of factors that reduce food intake, absorption of nutrients, or increase nutrient requirements. In PNG prior to, and at early stages of modernisation, primary malnutrition is likely to have been the usual initiating factor in the onset of growth faltering due to undernutrition-infection interactions. However, the possibility that infection may have been the initiating event in some societies cannot be excluded. This would have happened by way of early dietary supplementation of infants with foods of minor nutritional significance, which could have acted as a vehicle for the introduction of infectious disease to the child. With modernisation and adoption of primary health care principles, earlier supplementation of infant diet than was previously the case became common in PNG. This has lead to general improvements in growth and nutritional status. However, in populations where undernutrition is still common, infection has become more important than primary malnutrition as the initiator of growth faltering due to undernutrition-infection interactions.